2010
DOI: 10.1063/1.3454774
|View full text |Cite
|
Sign up to set email alerts
|

Carrier transport mechanisms of organic bistable devices fabricated utilizing colloidal ZnO quantum dot-polymethylmethacrylate polymer nanocomposites

Abstract: Organic bistable devices (OBDs) fabricated utilizing ZnO quantum dots (QDs) embedded in a poly(methyl methacrylate) (PMMA) layer were fabricated by using a spin-coating technique. Transmission electron microscopy images revealed that 5-nm-diameter ZnO QDs were formed inside the PMMA polymer layer. Current-voltage (I-V) measurements on Al/ZnO QDs embedded in PMMA layer/indium-tin-oxide devices at 300 K showed electrical bistability. The maximum ON/OFF ratio of the current bistability for the OBDs was as large a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 23 publications
2
24
1
Order By: Relevance
“…[44]. The value of on/off ratio reported for a two terminal device containing graphene quantum dots embedded in the matrix of poly(ethylene glycol) bis(carboxymethyl) ether between two gold electrodes in a planar structure operating at ±4.3V is at least three orders of magnitude smaller than the one obtained in the presented investigation [45].…”
Section: Bistable Electrical Behaviourcontrasting
confidence: 41%
“…[44]. The value of on/off ratio reported for a two terminal device containing graphene quantum dots embedded in the matrix of poly(ethylene glycol) bis(carboxymethyl) ether between two gold electrodes in a planar structure operating at ±4.3V is at least three orders of magnitude smaller than the one obtained in the presented investigation [45].…”
Section: Bistable Electrical Behaviourcontrasting
confidence: 41%
“…A simple ZnO nanostructure, nanoparticles or nano-powder, 75 has been successfully applied in organic optoelectronics due to 76 their excellent optical, electrical, mechanical and chemical proper-77 ties [17,18]. For organic memory application, some studies con- [19,20]. However, studies on the electrical bistabilities, the mem- been reported yet.…”
mentioning
confidence: 97%
“…19 The detailed formation process of the core-shell CIS-ZnS QD solution is described elsewhere. 20,21 After the synthesis of the CIS core solution was finished, the synthesized solution was in-situ cooled at room temperature to form the ZnS shell.…”
mentioning
confidence: 99%